Implementation traffic control and traffic shaping in linux using web approach / Eric Ng Kang Yin - Eric Ng, Kang Yin (2004)
This report firstly would give an overview or an introduction to the world of Linux, and then explaining more on the networking capabilities of Linux, more specifically the traffic control. Next, this report will review the essential knowledge behind the traffic control process in the literature review. These reviews include the operating systems, web servers, programming tools, and also a few existing systems concerning traffic control. Comparisons are made between the reviews mentioned above in order to make out which tools will be used to develop the system later on. The third part will describe the methodology used to develop this system, together with their explanations. The fourth part, which is the System Analysis, will list out the requirements of the system in order to continue to the next phase of the system development. Finally part 5 will be the system design where the flow of the system will be discussed and understood before embarking on the implementation phase. Following that would be system testing and system evaluation References are also included in order to clarify the details mentioned in this report.